Analysis of the System management data to improve the quality of health services in the Lospalos CHC, Lautém Municipality - Daniela Rolandia Maria Umbelina Fernandes; Marcos Carvalho (Public Health and Safety International Journal, 2025)
Quality services are vital indicators of healthcare quality, prompting both government and private sectors to focus on this issue. This research examines the data management system related to healthcare quality at the Lospalos Community Health Center in Lautém Municipality for the year 2021. Utilizing a quantitative analysis method with a cross-sectional approach, the study surveyed 43 healthcare personnel and applied univariate and bivariate analyses, specifically Chi-Square Analysis. The findings reveal that the management of data for health service quality was deemed poor, with a total score indicating poor management. In contrast, good management was represented by 97.6% of instances recorded. The analysis shows a significant relationship (p-value = 0.03) between effective data management (X variable) and quality of health attendance (Y variable). The study advocates for the Health Center Chief to prioritize compliance with established procedures and collaborate with the relevant Ministry to improve human resources and health facilities, ultimately enhancing service delivery and public health outcomes.